Biophysical and proteomic analyses of Pseudomonas syringae pv. tomato DC3000 extracellular vesicles suggest adaptive functions during plant infection - Janda, Martin; Rybak, Katarzyna; Krassini, Laura; Meng, Chen; Feitosa-Junior, Oséias; Stigliano, Egidio; Szulc, Beata; Sklenar, Jan; Menke, Frank L H; Malone, Jacob G; Brachmann, Andreas; Klingl, Andreas; et al. (mBio, 2023)
Vesiculation is a process employed by Gram-negative bacteria to release extracellular vesicles (EVs) into the environment. EVs from pathogenic bacteria play functions in host immune modulation, elimination of host defenses, and acquisition of nutrients from the host. Here, we observed EV production of the bacterial speck disease causal agent, Pseudomonas syringae pv. tomato (Pto) DC3000, as outer membrane vesicle release. Mass spectrometry identified 369 proteins enriched in Pto DC3000 EVs. The EV samples contained known immunomodulatory proteins and could induce plant immune responses mediated by bacterial flagellin. Having identified two biomarkers for EV detection, we provide evidence for Pto DC3000 releasing EVs during plant infection. Bioinformatic analysis of the EV-enriched proteins suggests a role for EVs in antibiotic defense and iron acquisition. Thus, our data provide insights into the strategies this pathogen may use to develop in a plant environment. IMPORTANCE The release of extracellular vesicles (EVs) into the environment is ubiquitous among bacteria. Vesiculation has been recognized as an important mechanism of bacterial pathogenesis and human disease but is poorly understood in phytopathogenic bacteria. Our research addresses the role of bacterial EVs in plant infection. In this work, we show that the causal agent of bacterial speck disease, Pseudomonas syringae pv. tomato, produces EVs during plant infection. Our data suggest that EVs may help the bacteria to adapt to environments, e.g., when iron could be limiting such as the plant apoplast, laying the foundation for studying the factors that phytopathogenic bacteria use to thrive in the plant environment.
Keywords: Solanum lycopersicum; Humans; proteomics; Proteomics; Pseudomonas syringae; NTA; Plant Diseases; Arabidopsis thaliana; lidé; proteomika; bakteriální proteiny; flagelin; extracelulární vezikuly; pattern-triggered immunity; Pto DC3000; Flagellin; nanoparticle tracking analysis; nemoci rostlin; Bacterial Proteins; extracellular vesicles; EVs; Extracellular Vesicles; PTI